Evaluation of Soils and Their Cover Before and After a Natural Disaster in Madagascar - Sebas David Rabotovao; Fridolin Andriazafinahazo; Rabevala Rajaonah; Aro Pascal Ratsimbazafy; Andrianjafimanjato Daniel Razafindrazanakolona; Baholy Robijaona Rahelivololoniaina (Britain International of Exact Sciences (BIoEx) Journal, 2025)
In Madagascar, the statistics on the natural disaster allowed us to determine the study area and the type of natural disaster to be treated in our study. The choice of the Vatovavy Region for our project treatment of the theme ‘’Evaluation of soils and its coverings before and after natural disaster Madagascar’’ is based on crucial considerations linked to its history of vulnerability to cyclones between 2006 and 2022. This region was particularly affected by these natural phenomena during this period, making it a suitable site for assessing the impact of natural disasters on soils and their covers. We aims to analyze the evolution of space observation of the Earth, focusing on technological advances of spatial remote sensing, spectral discrimination of satellite sensors, and the physical principles of remote sensing for agriculture. With a focus on Madagascar, it includes satellite identification relevant, the collection of spatial data, and the use of these data to characterize agricultural areas. The project highlights the benefits of remote sensing for agriculture, analyzes the evolution of coverage and land use, studies natural disasters, and maps land use between 2006 and 2022, in identifying the factors of change and prioritizing them according to their impact on land use.